The Transformative Teacher: Integrating Deep Learning Models into Contemporary Islamic Education - An Nisa Rahmadani (Akademika : Jurnal Keagamaan dan Pendidikan, 2025)
Contemporary Islamic education can no longer rely solely on the textual and normative transmission of religious knowledge; instead, it must be redirected toward active, reflective, contextual, and transformative learning paradigms. This study employs a descriptive-qualitative library research method, analyzing various scholarly articles, books, theses, and online media documentation. The findings indicate that contemporary Islamic learning demands teachers to function as facilitators, value mediators, and agents of transformation who guide students in comprehending, internalizing, and practicing Islamic teachings within classroom interactions and daily life. Specifically, the deep learning model demonstrates strong conceptual relevance in Islamic education as it enables students to construct profound understanding, cultivate critical reasoning, strengthen spirituality, and actualize Islamic values in response to social and moral challenges. Each analyzed learning model offers distinct yet complementary contributions to forming a holistic, meaningful, and welfare-oriented Islamic education. Consequently, this article asserts that the development of contemporary Islamic learning requires integrative and transformative pedagogical designs to ensure that Islamic education produces a generation that is not only faithful and virtuous but also intellectually critical and adaptive to the complexities of the modern era.